Sengketa Lembaga Negara Antara Komisi Yudisial Dengan Mahkamah Agnng - Riri Nazriyah (Jurnal Hukum IUS QUIA IUSTUM, 2006)
Constitutionally, the institution which has an authority to settle dispute between institutions is Constitutional Court. However, in the dispute between Judicial Commission and Supreme Court, the Constitutional Court is not able to handle the case. Because there is an exception of article 65 Constitutional Court.